Analisis Pengaruh Tingkat Pendidikan, Tingkat Kesehatan dan Jenis Kelamin Terhadap TPAK di Sumatera Barat - Fuada, Nurul; Amar, Syamsul (Jurnal Kajian Ekonomi dan Pembangunan, 2024)
This Study aims to determine and analyze the effect of Education Level,Health Level and Gender on Labor Force Participation  Rate in West Sumatera. This research uses panel data from  2017-2021  in 19  regencies/citiesin West Sumatera which are sourced from the central bureau of statistics. Before using the regression, the Chow test and Hausman test were carrid out and the results of the analysis showed that the selected model was the Random Effect Model (REM). The results of the study reveal that : (1) Education Level has a significant effect on the Labor Force Participation Rate in West Sumatera (2) Health Level has no significant effect on  the Labor Force Partisipation Rate in west Sumatera (3) Gender has a significaneffect on the Labor force Partisipation Rate in West Sumatera. These finding confirm the role of the labor force is suggested to the Government that it is necessary to increase the ease of access to education for the community. So that in the future there will be an increase in  Labor Force Participation Rate in West Sumatera.